The history and the problems of Bantu urban secondary education in the Eastern Cape, 1937-1954 (Ciskei region) - Dyasi, Hubert Mongameli (Rhodes University, Faculty of Education, Department of Education, 1961)
1. Reasons for Choosing the Topic. Much has been written about secondary education in England, Continental Europe, the United States, Canada, China and other countries mainly "because Secondary Education has been one of the most prized of all formal types of education ... because it has been the rung of the educational ladder that has led to opportunity and preferment". Very little research work has been done on Bantu secondary education in the Ciskei, and still less about Bantu urban secondary education. This is a shortcoming since the Ciskei has been one of the most important educational areas for the Bantu in the Union of South Africa and the territories outside her borders. It was here that the experiment of Bantu day secondary schools was carried out. It could aptly have been said of the Ciskei, too, that "experimental work (destined one day to blaze into a consuming fire) has been carried on, where men and women of faith and inspiration have lit up some dark corner of the field, and where teachers of genius have defied tradition and convention, gone their own way in scorn of consequence, and have lit a candle which will never be put out". The Bantu Urban Day Secondary Schools started amidst conflicting opinions as regards their advantages and disadvantages. Difficulties were encountered and efforts made to overcome them. The present writer attempts to show how the problems of these schools were overcome and to assess the progress that was made. 2. Need for the Study. There is a great need for the study of the history and problems of Bantu Urban Day Secondary education because for many years to come these schools will have to serve an increasing number of urban Bantu pupils. The results of the research may serve as a guide to teachers appointed to these schools. The important history of these institutions preserved only in the minds of old men and women, may be lost to posterity. There is also a great need to bring to light the unique problems confronting these schools. 3. Scope of Dissertation. The dissertation limits itself to Bantu Urban Day secondary education, in specific areas of the Ciskei. Two secondary and two high schools have been chosen for special study. Bantu Urban Day Secondary Schools are those schools which are situated in areas under the jurisdiction of municipalities or town councils irrespective of whether the school admits largely pupils who are outside such an area or only those within it or both. The entrance qualification to these schools has always been a pass in Standard VI (normally after eight years of primary or elementary schooling). For the Bantu pupil the Junior Certificate Course was of three years' duration. The successful completion of the J.C. course qualified pupils to train as nurses, in the case of girls, and agricultural demonstrators in the case of boys. Both sexes could undertake studies for Native Primary Higher Teachers' Course, and the Senior Certificate Course or the Matriculation leading to university degrees.
Keywords: Black people -- Education -- South Africa -- Ciskei; Black people -- Education -- South Africa -- Eastern Cape -- History